PENDIDIKAN MASYARAKAT DAN TRAUMA HEALING PADA KORBAN BANJIR PEKALONGAN DI PENGUNGSIAN TAHUN 2021 - Alfira Nuril Aissya, Alfira Nuril Aissya (Jurnal Muhammadiyah untuk Olahraga Indonesia, 2021)
Flood disaster in Pekalongan City in February 2021 has been going onfor more than 1 week. Several evacuation posts have been prepared toaccommodate people affected by the flood. The floods that occurred amid theCovid-19 pandemic caused anxiety and concern, both adults and children alsofelt the impact of the flood, as a result most residents forgot their PHBS habits(clean and healthy lifestyle) and did not comply with the 4M health protocol(wearing masks, washing hand, keep your distance, and avoid crowds) when youare at the evacuation post. This situation cannot be allowed to drag on, theconstant anxiety and worry can lower a person's immunity so that he has theopportunity to contract the Covid-19 virus. The purpose of this service is toremind the public of the importance of maintaining PHBS (a clean and healthylifestyle) and complying with the 4M health protocol (wearing masks, washinghands, keeping distance, avoiding crowds), and reducing community anxiety andconcern. The method used in this service is community education related toPHBS and 4M as well as trauma healing by doing creative aerobic exercises.The result of this service is increasing public awareness regarding theimplementation of PHBS (a clean and healthy lifestyle) and continuing to carryout 4M (wearing masks, washing hands, maintaining distance, avoiding crowds)in refugee environments and increasing physical fitness, and providing joy, sothat these activities help reduce the anxiety, worry and fear experienced bypeople affected by flooding